Evidence-Based Practice Profile of Physiotherapist in Indonesia: A Descriptive Study - Condrowati Condrowati; Farahdina Bachtiar; Purnamadyawati Purnamadyawati; Ailsa Nahda Ahnafa Amsah; Jihan Ari Utami (Program Pendidikan Vokasi Universitas Indonesia, 2022)
Evidence-based practice (EBP) is a foundational element of a healthcare practitioner to support the clinical adjustment. Evidence-based physiotherapy is integrated between high-quality clinical research, patients' preferences, and clinical expertise. However, in Indonesia, evidence-based practice profiles in physiotherapy have not been explained by the previous study. The current study aimed to identify the evidence-based practice profiles of physiotherapists in Indonesia. The study was descriptive quantitative. The design study used was a cross-sectional study. The inclusion criteria were physiotherapists work in Indonesia, age no more 65 years old (≤ 65 years old), whereas the exclusion criteria were the physiotherapists who were not acting as a physiotherapist and refused to be a respondent. The evidence-based practice questionnaire was distributed by using Google Form. The questionnaire included 11 questions. Most of the physiotherapists attending the course or training were 110 participants (77.5%), joining as a member of physiotherapy organization with the percentage at 95.8%. Most physiotherapists also have specialization areas in the physiotherapy field in which the highest proportion is in musculoskeletal physiotherapy. The experiences of the physiotherapists who participated in the study showed the various years of work, the variation of the average hours of work, and the various numbers of patients treated each day. In addition, most of the physiotherapists read or reviewed the research articles around 2 to 5 articles each month. The study concluded that the physiotherapists in Indonesia were active to participate in any kind of personal improvement like attending the courses or training, joining as a member of physiotherapy organization. Most physiotherapists also have specialization areas in the physiotherapy field. The thing that needs improvement of the physiotherapist is the awareness to consider the scientific research or literature to support their clinical decision when the physiotherapists care for the patients.Keywords: evidence-based practice, physiotherapy, physiotherapist, profiles